2018
DOI: 10.1007/978-1-4939-7614-0_15
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Fatty Liver in Models of Disease Programming

Abstract: Nonalcoholic fatty liver disease (NAFLD) is currently the most common cause of chronic liver disease worldwide and is present in a third of the general population and the majority of individuals with obesity and type 2 diabetes. Importantly, NAFLD can progress to severe nonalcoholic steatohepatitis (NASH), associated with liver failure and hepatocellular carcinoma. Recent research efforts have extensively focused on identifying factors contributing to the additional "hit" required to promote NALFD disease prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 51 publications
2
2
0
Order By: Relevance
“…The OVX group compared to the SHAM group showed tissue lipid accumulation between body weight and increased abdominal fat, as described in previous other studies [ 1 , 43 ]. The estrogen treatment with OVX prevented weight gain and increased adiposity.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The OVX group compared to the SHAM group showed tissue lipid accumulation between body weight and increased abdominal fat, as described in previous other studies [ 1 , 43 ]. The estrogen treatment with OVX prevented weight gain and increased adiposity.…”
Section: Discussionsupporting
confidence: 86%
“…Based on in vitro experimental results, we attempted to confirm the results in an in vivo system of a menopause animal model in which nonalcoholic fatty liver was induced. Evidence-Based Complementary and Alternative Medicine e OVX group compared to the SHAM group showed tissue lipid accumulation between body weight and increased abdominal fat, as described in previous other studies [1,43]. e estrogen treatment with OVX prevented weight gain and increased adiposity.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Diet, besides its impact on health and disease, can also influence the offspring's phenotype, depending on what the mother ate during gestation and lactation periods (1)(2)(3) . Experimental models showed that it is expected to find phenotypes of body weight loss in the neonate and obesity and cardiometabolic risk in the offspring whose maternal diets were poor in proteins (12) , rich in fats (13) and Western diet style (14) , respectively. A similar process occurs between diet and BAT: diet can stimulate (15) and programme the development of this tissue, as it can act directly on the uncoupling protein 1 (UCP-1) (16) .…”
mentioning
confidence: 99%